2012
DOI: 10.1111/dom.12017
|View full text |Cite
|
Sign up to set email alerts
|

Metformin vs. insulin in gestational diabetes. A randomized study characterizing metformin patients needing additional insulin

Abstract: Metformin is an effective alternative to insulin in the treatment of GDM patients. Serum fructosamine may help in predicting the adequacy of metformin treatment alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
215
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(230 citation statements)
references
References 18 publications
10
215
1
4
Order By: Relevance
“…Recently, several RCTs have compared metformin and insulin as a treatment of GDM [36][37][38][39][40][41][42]. According to these RCTs, metformin seems to be comparable to insulin as regards glycaemic control and neonatal outcomes, while being associated with less maternal weight gain and lower rates of neonatal hypoglycaemia and, possibly, gestational hypertension.…”
Section: Medical Treatment Of Gdmmentioning
confidence: 99%
“…Recently, several RCTs have compared metformin and insulin as a treatment of GDM [36][37][38][39][40][41][42]. According to these RCTs, metformin seems to be comparable to insulin as regards glycaemic control and neonatal outcomes, while being associated with less maternal weight gain and lower rates of neonatal hypoglycaemia and, possibly, gestational hypertension.…”
Section: Medical Treatment Of Gdmmentioning
confidence: 99%
“…После исследования MIG было опубликовано мно-жество РКИ, посвященных сравнению метформина с инсулином, которые в большинстве своем подтвердили данные MIG [16][17][18][19][20][21][22][23]. Единственным ключевым отли-чием стало отсутствие тенденции к преждевременному родоразрешению в группе пациенток на метформине, которое было показано в MIG.…”
Section: репродуктивное здоровьеunclassified
“…Various studies have shown a wide range of incidence of about 1% to 14%. [3][4][5][6] GDM is associated with increased risk of adverse maternal and neonatal outcomes e.g., it increases the risk of preeclampsia, caesarian section and type 2 diabetes after pregnancy. Regarding neonatal outcomes, it can increase the risk of still birth, neonatal death, congenital defects, macrosomia, neonatal hypoglycemia and shoulder dystocia.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in neonatal weight after use of metformin has been reported by some studies. [2][3][4][5] But some studies have documented normal weight of neonates after metformin therapy.…”
Section: Introductionmentioning
confidence: 99%